Risk Factors and Anticoagulation Therapy in Patients With Isolated Distal Deep Vein Thrombosis in the Early Post-operative Period After Thoracic Surgery - Li, Yuping; Ding, Junrong; Shen, Lei; Yang, Jian; Wang, Haifeng; Zhou, Yiming; Jiang, Gening; Zhu, Yuming; Wang, Yin (Frontiers in Surgery, 2021)
Background Isolated distal deep vein thrombosis (IDDVT) accounts for approximately 50% of all patients diagnosed with deep venous thrombosis (DVT), but the diagnosis and optimal management of IDDVT remains unclear and controversial. The aim of this study was to explore potential risk factors and predictors of IDDVT, and to evaluate different strategies of anticoagulation therapy. Methods A total of 310 consecutive patients after thoracic surgery, who underwent whole-leg ultrasonography as well as routine measurements of D-dimer levels before and after surgery were evaluated. The general clinical data, anticoagulant therapy, pre- and postoperative D-dimer levels were collected. Differences between IDDVT, DVT and non-DVT groups were calculated. Logistic regression analysis was used to analyze risk factors of postoperative IDDVT. Results Age and postoperative D-dimer levels were significantly higher in IDDVT group than in non DVT group (p=0.0053 and p<0.001 respectively). Patients with IDDVT showed Logistic regression analysis showed that postoperative D-dimer level was a significant independent predictor of IDDVT even when adjusted for age and operation method (p = 0.0003). There were no significant side effects associated with either of the regimens. Half-dose therapy was associated with a significant decrease in the requirement for anticoagulation medications after discharge (p=0.0002). Conclusion Age and D-dimer levels after surgery are strong predictors of IDDVT following thoracic surgery. Half-dose therapeutic anticoagulation has the same efficiency in preventing IDDVT progression, is not associated with any additional risks of adverse effects compared to a full-dose regimen, and may be adopted for treating IDDVT patients after thoracic surgery.